2020
DOI: 10.1371/journal.pone.0243784
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of alcohol and binge drinking among pregnant women in Addis Ababa, Ethiopia: Prevalence and determinant factors

Abstract: Introduction People in Ethiopia, including pregnant women, highly consume both home-made and manufactured alcohol beverages due to lack of awareness about the harmful effect of risky alcohol use, and cultural acceptance of alcohol consumption. Alcohol consumption and other hazardous patterns of use like binge drinking have tremendous adverse effects on fetus and mothers. Therefore, this study aimed to assess the magnitude of alcohol consumption, binge drinking and its determinants among pregnant women residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…Many pregnancies are unplanned, and not all women recognize their pregnancy during the early stages. People may also have limited awareness about the harms associated with alcohol use during pregnancy ( Bitew et al, 2020 ), or may have received conflicting information from the media or health care professionals ( Elek et al, 2013 ). Although other disabilities have been associated with SDHs in that SDHs can be influenced by disability status ( Frier et al, 2018 ), or may impact caregiver beliefs ( Zuckerman et al, 2015 ) and wellbeing ( Spencer et al, 2021 ), with FASD, compromised SDHs are uniquely associated as potentially causal factors.…”
Section: Complexities Of Fetal Alcohol Spectrum Disordermentioning
confidence: 99%
“…Many pregnancies are unplanned, and not all women recognize their pregnancy during the early stages. People may also have limited awareness about the harms associated with alcohol use during pregnancy ( Bitew et al, 2020 ), or may have received conflicting information from the media or health care professionals ( Elek et al, 2013 ). Although other disabilities have been associated with SDHs in that SDHs can be influenced by disability status ( Frier et al, 2018 ), or may impact caregiver beliefs ( Zuckerman et al, 2015 ) and wellbeing ( Spencer et al, 2021 ), with FASD, compromised SDHs are uniquely associated as potentially causal factors.…”
Section: Complexities Of Fetal Alcohol Spectrum Disordermentioning
confidence: 99%
“…Previous studies have pinpointed that people in Ethiopia, including pregnant women, have highly consumed both home-made and manufactured alcoholic beverages due to a lack of awareness about the harmful effects of alcohol use and cultural acceptance of alcohol consumption in Kolfe sub-city, Addis Ababa, Ethiopia. As the findings revealed, the prevalence of alcohol consumption, binge-drinking and weekly alcohol consumption of four or more units among pregnant women was 39.78 percent, 3.54 percent and 4.9 percent, respectively [ 13 ]. The possible reasons for these discrepancies are variations in the educational status, culture, and socio-economic status of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a higher magnitude of alcohol consumption among pregnant women. The prevalence of binge drinking and the amount and frequency of drinking per week among pregnant women was also higher [14].…”
Section: Introductionmentioning
confidence: 95%